Clinical utility of fixed-dose combinations in hypertension: evidence for the potential of nebivolol/valsartan - Varagic J; Punzi H; Ferrario CM (Dove Medical Press, 2014)
Jasmina Varagic,1–3 Henry Punzi,4,5 Carlos M Ferrario2,3,61Hypertension and Vascular Research Center, 2Division of Surgical Sciences, 3Department of Physiology and Pharmacology, Wake Forest University, Winston-Salem, NC USA; 4Trinity Hypertension and Diagnostic Research Center, Carrollton, TX, USA; 5Department of Family and Community Medicine, University of Texas Southwestern Medical Center, Dallas, TX, USA; 6Department of Internal Medicine and Nephrology, Wake Forest University, Winston-Salem, NC, USAAbstract: Despite significant advances in pharmacologic approaches to treat hypertension during the last decades, hypertension- and hypertension-related organ damage are still a high health and economic burden because a large proportion of patients with hypertension do not achieve optimal blood pressure control. There is now general agreement that combination therapy with two or more antihypertensive drugs is required for targeted blood pressure accomplishment and reduction of global cardiovascular risk. The goals of combination therapies are to reduce long-term cardiovascular events by targeting different mechanism underlying hypertension and target organ disease, to block the counterregulatory pathways activated by monotherapies, to improve tolerability and decrease the adverse effects of up-titrated single agents, and to increase persistence and adherence with antihypertensive therapy. Multiple clinical trials provide evidence that fixed-dose combinations in a single pill offer several advantages when compared with loose-dose combinations. This review discusses the advances in hypertension control and associated cardiovascular disease as they relate to the prospect of combination therapy targeting a third-generation beta (β) 1-adrenergic receptor (nebivolol) and an angiotensin II receptor blocker (valsartan) in fixed-dose single-pill formulations.Keywords: blood pressure control, hypertension, β1-adrenergic receptor, renin angiotensin system, fixed-dose combination therapy, nebivolol, valsartan